Urethroplasty by midline longitudinal incision of the dorsal wall of urethra at the site of the fistula: A useful adjunct to the conventional method of repair of urethrocutaneous fistula developing after hypospadias surgery - Sarkar Ruchirendu; Konar H; Sahabasu K; Saha K; Samanta N (Wolters Kluwer Medknow Publications, 2006)
In cases of repair of urethrocutaneous fistulae developing after primary hypospadias surgery, tubularisation often becomes difficult after excision of scar tissue. It is also well-known that this type of fistulae has a high recurrence rate. In this study of 15 cases, the aim is to analyze the results of conventional urethrocutaneous fistula repair, augmented with the principle of Midline longitudinal incision of the dorsal wall of the urethra at the site of the fistula according to the concept of Tubularised Incised Plate Procedure with the hope of preventing recurrence. Here, the excision of scar tissue around the urethrocutaneous fistulae, tubularisation of urethra is done after incising the dorsal urethral plate. Then the mucosa is closed over a 6F/8F catheter and the resultant suture line is covered first with the dartos flap or adjacent tissue and then, the skin. The skin layer is minimally rotated so as to avoid suture-line overlap. Results of this method has been found to be quite satisfactory, as only in two[2] patients the fistula recurred. Thus it may be concluded from this study that the Tubularised Incised Plate Urethroplasty along with conventional urethral fistula repair is a good adjunctive procedure in prevention of their recurrence.